O sofrimento psíquico no trabalho em profissionais de saúde mental: estudo de caso em um CAPS adulto no interior do estado do Paraná - Silveira, Márcio Alves (2021)
This research aims to investigate the psychic suffering of these professionals who work supporting the mental health of the assisted population and, as specific objectives, to identify the different dimensions of psychic suffering linked to the work of these workers, understand how they deal with mental suffering and identify aspects of suffering and pleasure at work. It is a qualitative, interpretative and empirical research, using as instruments participant observation, semi-structured interviews and application of the Inventory of Risks of Pathogenic Suffering at Work (IRIS), the latter being used to analyze three factors closely related to work: usefulness, unworthiness and recognition, which refer respectively to the feeling of appreciation and satisfaction at work, feeling of injustice and dissatisfaction and finally, feeling admired and accepted with their work; the interviews allowed to investigate details of the daily work routine, as well as affections involved in this dimension, and were worked from the Thematic Content Analysis; the participant observation occurred during 14 days in all shifts (morning/afternoon/night) and days of the week (including Saturday and Sunday) through the monitoring of workers and questioning when the researcher felt necessary and allowed to understand the routine of the Institution, aspects of the prescribed work and the real work. The discussion of the results was supported by the theoretical referential of Work Psychology, Psychodynamics of Work and Psychosocial Care; we also used the Marxist conception of work as the basis of our theoretical referential. This research made it possible to understand that the pathogenic suffering of the participating workers has its source in emotional wear, causes of frustration and sadness, in the overload for a volume of work of a city that needs more CAPS Adult, in the fragmented work being taken by dead work and precarious bonds; but also a work activity capable of bringing satisfaction to the extent that the living work and the praxis allow the transformation of reality and promote greater learning; the research provided the perception that the dialectic pleasure / suffering is present in work relationships, permeated by living work and dead work.